Solution of Mechanical Systems with Uncertainty Parameters Using IFEA - Milan Vasko; Milan Saga (Communications - Scientific letters of the University of Zilina, 2009)
The paper presents a non-traditional computational approach for structural analysis with uncertainties in material, geometry and load parameters. Uncertainties are introduced as bounded possible values - intervals. The main goal is to propose algorithms for interval computations on FEM models suggested by authors. An application of the chosen approaches is presented - the first one, a simple combination of only inf-values or only sup-values; the second one presents full combination of all inf-sup values; the third one uses the optimisation process as a tool for finding out a inf-sup solution and last one is Monte Carlo technique as a comparison tool.